Über Verteilung der Basiselemente in den freien Zahlenhalbgruppen. III - Cibulskytė, D. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Д. Цибульските. О распределении образующих элементов в свободных числовых полугруппах. III D. Cibulskytė. Laisvos skaitinės pusgrupės generuojančių elementų pasiskirstymo klausimu III